2020
DOI: 10.1080/14756366.2020.1747449
|View full text |Cite
|
Sign up to set email alerts
|

6,7-Dimethoxy-2-phenethyl-1,2,3,4-tetrahydroisoquinoline amides and corresponding ester isosteres as multidrug resistance reversers

Abstract: Aiming to deepen the structure-activity relationships of the two P-glycoprotein (P-gp) modulators elacridar and tariquidar, a new series of amide and ester derivatives carrying a 6,7-dimethoxy-2-phenethyl-1,2,3,4-tetrahydroisoquinoline scaffold linked to different methoxy-substituted aryl moieties were synthesised. The obtained compounds were evaluated for their P-gp interaction profile and selectivity towards the two other ABC transporters, multidrug-resistance-associated protein-1 and breast cancer resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Although several compounds showed potent and selective efficacy for the P-gp transporter, only four compounds (14, 87 The mechanism of MDR modulation of all of the abovementioned compounds was due to an inhibition of P-gp-mediated drug efflux. 84,85,87,89 In addition, 16 inhibited P-gp ATPase activity without affecting P-gp expression. 84 In silico analyses, such as molecular docking and dynamic stimulation, indicated that 16 formed a long-lasting interaction with P-gp via hydrophobic interactions and hydrogen bond contacts.…”
Section: Compounds With a Tetrahydroisoquinoline Scaffoldmentioning
confidence: 96%
See 3 more Smart Citations
“…Although several compounds showed potent and selective efficacy for the P-gp transporter, only four compounds (14, 87 The mechanism of MDR modulation of all of the abovementioned compounds was due to an inhibition of P-gp-mediated drug efflux. 84,85,87,89 In addition, 16 inhibited P-gp ATPase activity without affecting P-gp expression. 84 In silico analyses, such as molecular docking and dynamic stimulation, indicated that 16 formed a long-lasting interaction with P-gp via hydrophobic interactions and hydrogen bond contacts.…”
Section: Compounds With a Tetrahydroisoquinoline Scaffoldmentioning
confidence: 96%
“…Moreover, the removal of the 6,7‐dimethoxy group or the replacement of the tetrahydroisoquinoline with tetrahydroquinoline significantly decreased the potency. Although several compounds showed potent and selective efficacy for the P‐gp transporter, only four compounds ( 14 , 87 15 , 85 16 , 84 and 17 , 89 Figure 4B) were found to reverse P‐gp‐mediated MDR in cancer cells. Specifically, 14 restored DOX efficacy in P‐gp‐overexpressing DOX‐resistant glioblastoma and malignant pleural mesothelioma stem cells 90,91 at nanomolar concentrations.…”
Section: P‐gp Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside their applications as analgesics and antitussives,[ 1 , 2 , 3 , 4 ] THIQs show promise as therapeutics towards cancer, neuropathologies and multi‐drug resistant bacteria. [ 3 , 5 , 6 , 7 , 8 ] However, supply of these compounds for studies and clinical use is limited. Natural THIQs can be harvested from mixtures from certain plants, but their chemical syntheses are complicated by the presence of chiral centres and the density of functional groups.…”
Section: Introductionmentioning
confidence: 99%